“One thing leads to another”, but where?~–~Gateway cities and the geography of production linkages - Moritz Breul; Javier Revilla Diez (Growth and Change, 2021)
Although it has been argued that current configurations of extractive industries provide opportunities for developing production linkages, in other words, that “one thing leads to another”, these opportunities are not necessarily realised directly in the resource-holding countries. This article aims to explain why the greater opportunities for creating increased production linkages may remain unrealised. While existing research on production linkages is characterised by a national scale mode of analysis, this article examines production linkages in the resource-poor gateway city of Singapore that are intended to serve oil and gas operations at the macro-regional level in Indonesia and Vietnam. The results reveal that a significant depth and breadth of production linkages have unfolded in Singapore, highlighting that in particular sophisticated production linkages tend to have a broader geographic scope. Moreover, the analysis identifies factors that have shifted the territorial scale of labour-intensive and low-technology production linkages from a macro-regional towards a national or subnational level, to the advantage of the resource-holding countries. These insights add some complexity to the study of production-linkage development and emphasise the need for a multi-scalar perspective that does not stop at national borders.
Keywords: 300